Potential of liquid organic fertiliser from Maja fruit (Aegle marmelos) for rice crops / Sri Rahayu, Purwaningsih and Agus Suyanto - Sri Rahayu; Purwaningsih; Agus Suyanto (Penerbit PRESS, Universiti Teknologi MARA, 2024)
The difficulty in obtaining fertiliser fuelled creativity to utilise local potentials around farmers. One of them is to utilise the potential of maja fruit, which has been traditionally used only for its peel as a container for coconut sap, while its inner content is discarded. The aim of this research was to exploit the potential of maja fruit waste as liquid fertiliser and to determine the best concentration of liquid fertiliser produced from maja fruits for optimum rice crop production. This research was conducted at the Faculty of Agriculture, Tanjungpura University, and continued in Sungai Rengas Village, Kubu Raya Regency, West Kalimantan. The research was carried out for approximately five months, from May to September 2022. This research was conducted using the completely randomised design which consisted of M0 = control (synthetic fertiliser), M1 = 18 mL L−1, M2 = 24 mL L−1, M3 = 30 mL L−1, and M4 = 36 mL L−1, with three replications and a total of three sample plants. Observations were made on plant height, number of tillers, number of productive tillers per clump, bunch weight per clump, number of grains per bunch, and 1000-grain weight. The results showed that plants fertilised with liquid fertiliser derived from maja fruit surpassed the performance of plants fertilised with synthetic fertiliser. Among the different treatments of liquid organic fertiliser from maja fruit, the application of 30 mL L−1 concentration proved effective for rice crops, making it a viable alternative to synthetic fertilisers.